Synthesis of Tosyl- and Nosyl-Ended Polyisobutylenes with High Extent of Functionalities: The Effect of Reaction Conditions - Balázs Pásztói (Polymers, 2020)
Endfunctional polymers possess significant industrial and scientific importance. Sulfonyl endgroups, such as tosyl and nosyl endfunctionalities, due their ease of substitution are highly desired for a variety of polymer structures. The sulfonylation of hydroxyl-terminated polyisobutylene (PIB-OH), a chemically and thermally stable, biocompatible, fully saturated polymer, with tosyl chloride (TsCl) and nosyl chloride (NsCl) is presented in this study. PIB-OHs derived from commercial exo-olefin-ended PIB (PIBexo-OH) and allyl-terminated polymer made via quasiliving carbocationic polymerization of isobutylene (PIBall-OH) were tosylated and nosylated in the presence of 4-dimethylaminopyridine (DMAP), pyridine and 1-methylimidazole (1-MI) catalysts and triethylamine (TEA). Our systematic investigations revealed that the end product distribution strongly depends on the relative amount of the components, especially that of TEA. While PIBexo-OTs with quantitative endfunctionality is readily formed from PIBexo-OH, its nosylation is not as straightforward. During sulfonylation of PIBall-OH, the formed tosyl and nosyl endgroups are easily substituted with chloride ions, formed in the first step of sulfonylation, leading to chloride termini. We found that decreased amounts of TEA afford the synthesis of PIBall-OTs and PIBall-ONs with higher than 90% endfunctionalities. These sulfonyl-ended PIBs open new ways for utilizing PIB in various fields and in the synthesis of novel PIB-containing macromolecular architectures.